Tafsir al-Ṭabarī dan Riwayat Problematik: Pendekatan Intertekstual dalam Tradisi Naratif menurut McAuliffe - Zaiyadi, Ahmad; Kunti Rofikoh (Journal of Islamic Scriptures in Non-Arabic Societies, 2025)
This article examines the story of the Prophet Muhammad’s ﷺ marriage to Sayyidah Zainab bint Jahsh as narrated in QS. al-Aḥzāb: 37–38, employing a narrative-critical approach to Tafsīr al-Ṭabarī, with a primary focus on problematic ḥadīths (al-dakhīl) that have shaped interpretations of the text. One of the contested reports suggests that the Prophet ﷺ fell in love with Zainab after seeing her unveiled—an account that lacks a sound chain of transmission and directly contradicts the doctrinal principle of prophetic infallibility (ma‘ṣūmiyyah). Unlike Isrā’īliyyāt, which stem from Judeo-Christian traditions, these problematic reports originate from within early Islamic narratives and were often transmitted uncritically in classical exegesis. Using Jane Dammen McAuliffe’s framework—emphasizing intertextuality and narrative framing—this study argues that classical tafsīr is not ideologically neutral, but shaped by selective citation and narrative construction that can obscure the theological intent of the Qur’anic text. Accordingly, tafsīr is understood not merely as an exegetical explanation of scripture, but as a discursive space where meaning and authority are continually negotiated. The article concludes that a critical re-reading of the Zainab episode is necessary to cleanse it of unsound reports and to reaffirm its Qur’anic purpose: the abrogation of pre-Islamic adoption practices (tabannī) and the establishment of divine law above inherited social norms.